Socio-Cultural Factors Influencing Primary Graders’ Ability in English Skills - Marsya Amanta Zahrani Salsabila; Aswir (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2024)
This research investigated sociocultural factors' influence on language learners' abilities, specifically in the context of English education in Indonesia. The various social backgrounds of Indonesians posed difficulties in English instruction due to differences in communication standards. The research aimed to determine social and cultural factors that impacted the English language skills of primary-grade students by providing insights into the educational context at SD Smart School Jakarta. It employed a descriptive qualitative technique within a case study research design. The research comprised two English teachers and grades 5 consisting of 56 students. Through data analysis and engaging in conversations, the study highlighted the crucial significance of motivation in overcoming obstacles in both speaking and writing. An inclusive English learning environment incorporating various methodologies was advantageous for students. Moreover, the active participation of parents was identified as a crucial element in improving the English language skills of elementary school students. The results emphasized the importance of motivation, a favorable learning environment, and parental assistance in acquiring English language proficiency.